Changes as a Condition for Economic Development of Bazaars - Prdić, Nedeljko (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The problem of the research is the adaptation of bazaars to market changes which are an integral part of the development of trade in agriculture. The aim of the research is to define the strategy of bazaar development by changes in business, based on the analysis of theoretical attitudes and research results. The conceptual model of development derives from experiential knowledge and research results. The research is primarily based on the use of a comparative method of marketing research with a combination of historical and research methods. The traditional application of the historical method is observing the current state of bazaars through inertia, which consists in monitoring and comparing the state of bazaars in previous years and rhetorically, which implies predicting that competing companies will endanger bazaars as a marketing channel in the market. The results of the research provided a reliable basis and the conclusion that changes in the bazaar business are necessary. Namely, bazaars are a historical and modern marketing instrument in the trade of agricultural products, so it is necessary to adopt changes in business that will maintain a competitive advantage in the market. The conclusion is that the changes presuppose the basis of the economic development of the bazaar by monitoring the competing companies on the basis of the traditional importance on the market of agricultural products and the satisfaction of the consumers.